Effects of Oxygen Concentration and Culture Time on Porcine Nucleus Pulposus Cell Metabolism: An in vitro Study - Jaworski, Lukas M.; Kleinhans, Kelsey L.; Jackson, Alicia R. (Frontiers in Bioengineering and Biotechnology, 2019)
Low back pain is a common ailment that affects millions of individuals each year and is linked to degeneration of the intervertebral discs in the spine. Intervertebral disc degeneration is known to result from an imbalance in anabolic and catabolic activity by disc cells. Due to the avascular nature of the intervertebral disc, oxygen deficiency may occur in the central nucleus pulposus (NP). Resulting hypoxia affects matrix regulation and energy metabolism of disc cells, although the mechanisms are not fully understood. This study investigates in vitro glucose consumption and gene expression by NP cells over time under varying oxygen tensions. Notochordal porcine NP cells were cultured in agarose discs at 21%, 5% or 1% oxygen tension for 1, 5, or 10 days. The expression of ten key matrix genes, as well as Brachyury (T), by cells was analyzed using RT-PCR. Glucose consumption was measured using a two-point method. Results show that culture time and oxygen tension significantly affect glucose consumption rates by porcine NP cells. There were also significant changes in T expression based on oxygen level and culture time. The 1% oxygen tension had a significantly higher T expression on day 10 than the other two groups, which may indicate a better maintenance of the notochordal phenotype. MMP 1 and 13 expression increased over time for all groups, while only the 5% group showed an increase over time for MMP 3. TIMP expression followed the direction of MMPs but to a lesser magnitude. 5% and 21% oxygen tensions led to decreases in anabolic gene expression while 1% led to increases. Oxygen concentration and culture time significantly impacted glucose consumption rate and the gene expression of matrix regulatory genes with hypoxic conditions most accurately maintaining the proper NP phenotype. This information is valuable not only for understanding disc pathophysiology, but also for harnessing the potential of notochordal NP cells in therapeutic applications.